Water splitting electrocatalyst and preparation method thereof
By preparing transition metal nitrogen/phosphide composite materials on metal foam substrates, forming a graded core-shell heterostructure micro-nano array, the problems of high catalyst cost, slow mass transfer and poor stability in industrial-scale electrolytic hydrogen production are solved. It achieves efficient and stable electrocatalytic performance of water cracking.
Patent Information
- Application Number
- CN202411576591.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-14
AI Technical Summary
The catalysts in industrial-scale electrolytic hydrogen production have high cost, slow mass transfer and poor stability, making it difficult to meet the reaction needs of cathode and anode under high current density.
Transition metal nitrogen/phosphide composite material with metal foam as the substrate is prepared by hydrothermal, nitriding and electrochemical deposition to form a graded core-shell heterostructure composed of firework-like nanosheets and rough surface nanorods. Micro-nano arrays.
It improves the activity, stability and electrochemical performance of the catalyst, realizes efficient electrocatalysis of water cracking, and has dual-function HER and OER electrocatalytic performance, stable performance and low cost.
Smart Images

Figure CN119433602A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrochemical hydrogen production, and in particular relates to a water splitting electrocatalyst and a preparation method thereof. Background Art
[0002] Exploring renewable energy to replace traditional fossil energy and developing renewable hydrogen with carbon-free carriers and high energy density has become an inevitable trend. Water electrolysis hydrogen production technology is regarded as one of the most promising renewable hydrogen production technologies due to its significant advantages such as simple operation and clean process. In order to improve the electrolysis efficiency in industrial production, it is usually operated for a long time (>100 hours) in an electrolyte with a high KOH concentration (20-40 wt%). Therefore, it is necessary to find cheap, efficient and stable catalytic materials to meet the high current density (>500 mA cm -2 ) under the cathode and anode (hydrogen evolution reaction: HER; oxygen evolution reaction: OER). More specifically, industrial-grade electrocatalysts must have sufficient active sites, exhibit fast charge-mass transfer rates, and have strong adhesion to the substrate to withstand the violent bubble impact generated during the electrolysis process. To achieve this goal, optimizing the catalyst components and designing a reasonable structure have become guiding principles in the catalyst synthesis process.
[0003] Transition metal nitrides have the characteristics of d-band contraction, strong stability, high conductivity and low cost, and show excellent HER catalytic performance, but their intrinsic activity is mostly lower than that of Pt-based catalysts. In recent years, improving their intrinsic catalytic activity through interface engineering and building heterostructures has become a research hotspot. Transition metal phosphides show HER / OER catalytic activity comparable to that of precious metal-based catalysts and also have the advantage of cost-effectiveness, but the traditional phosphating method requires high temperature treatment, has a long synthesis cycle and is accompanied by toxic gases during the reaction, which limits its feasibility in actual production. Electrochemical deposition is expected to replace the traditional phosphating method due to its simplicity and safety, but the material is prone to aggregation during the electrodeposition process, which is not conducive to exposing active sites. The use of porous metal current collectors such as metal foams to prepare self-supporting electrodes can promote electron transport and mass transfer and effectively expand the active area, but the interaction between the catalyst synthesized by electrodeposition and the smooth metal foam carrier is weak, resulting in poor stability.
[0004] Therefore, it is a very promising material design scheme to prepare transition metal phosphides by a simple and safe electrodeposition method, and to increase the loading of transition metal phosphides and the bonding strength with the substrate by introducing transition metal nitrides as template-modified metal foam substrates, thereby improving the excellent HER performance of transition metal nitrides while increasing the OER performance through a heterogeneous structure strategy, and preparing a highly stable industrial-grade HER and OER bifunctional water splitting electrocatalyst. Summary of the invention
[0005] In response to the problems of high catalyst cost, slow mass transfer and poor stability in industrial-scale water electrolysis to produce hydrogen, the invention provides a water splitting electrocatalyst and a preparation method thereof.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: A water splitting electrocatalyst is a transition metal nitrogen / phosphide composite material based on metal foam, which is in the shape of fireworks and is uniformly loaded on the metal foam.
[0007] Furthermore, in the transition metal nitrogen / phosphide composite material, the transition metal phosphide is a nanosheet, the transition metal nitride is a nanorod with a rough surface, the transition metal phosphide nanosheet grows vertically and uniformly on the surface of the transition metal nitride nanorod; the transition metal phosphide and the transition metal nitride are formed separately, and the two form a hierarchical core-shell heterostructure micro-nano array Furthermore, the electrocatalyst is a transition metal nitrogen / phosphide composite material supported by metal foam synthesized by hydrothermal, nitridation and electrochemical deposition.
[0008] A method for preparing a water splitting electrocatalyst comprises the following steps: Step 1, adding metal nitrate and polyoxometalate into deionized water and ultrasonicating them, then placing them into a metal foam substrate for hydrothermal reaction, cooling and drying them to obtain a precursor; Step 2, nitriding the precursor obtained in step 1 to obtain a transition metal nitride template supported by metal foam; Step 3, adding metal nitrate and sodium hypophosphite to deionized water, and transferring to an electrolytic cell after ultrasonication; using a transition metal nitride template supported by metal foam as a working electrode, a platinum sheet as a counter electrode, and Ag / AgCl as a reference electrode, a three-electrode system is used for constant voltage deposition, and after drying, a transition metal nitrogen / phosphide composite material supported by metal foam is obtained.
[0009] Furthermore, in the preparation method, metal nitrates and polyoxometalates are used as metal sources, ammonia is used as a nitrogen source, and sodium hypophosphite is used as a phosphorus source.
[0010] Furthermore, the metal nitrate is selected from ferric nitrate, cobalt nitrate or nickel nitrate; the polyoxometalate is selected from ammonium molybdate or ammonium tungstate; and the metal foam is selected from nickel foam, iron foam or copper foam.
[0011] Furthermore, in the step 1, the mass ratio of metal nitrate to polyoxometalate is 582-2328:353-1412; the reaction temperature of the hydrothermal reaction in the step 1 is 150-170° C., and the reaction time is 6-12 h.
[0012] Furthermore, in step 2, the temperature of the nitriding treatment is 500-700° C., and the reaction time is 1-3 h; in step 2, the environment of the nitriding treatment is argon as the protective gas, ammonia as the nitrogen source, and the argon / ammonia flow rate ratio is 2:1.
[0013] Furthermore, in the step 3, the mass ratio of metal nitrate to sodium hypophosphite is 175-1223:636-4452; the deposition voltage of the constant voltage deposition in the step 3 is -0.8-1.2 V, and the reaction time is 180-1800 s.
[0014] The application of water splitting electrocatalyst in the electrolysis of water for hydrogen evolution and oxygen evolution is characterized in that the electrolysis environment of the water electrolysis reaction is 1 M KOH - 25°C (laboratory) or 30% KOH - 60°C (industry).
[0015] Compared with the prior art, the present invention has the following advantages: The preparation method of the present invention has the advantages of simple and safe synthesis operation, high repeatability, large-scale preparation and low cost. By pre-templating the metal foam substrate, the transition metal phosphide can be uniformly grown on the template surface by only using a fast and non-toxic electrochemical deposition method.
[0016] In the preparation method of the present invention, during the electrochemical deposition process, transition metal phosphide nanosheets grow vertically and uniformly on the surface of transition metal nitride nanorods to form a micro-nano array structure. The structure has a large active specific surface area and can increase the reaction sites. The micro-nano array has the advantages of being air-phobic and hydrophilic, and has the ability of faster charge and gas-liquid transmission, thereby improving the electrochemical and mechanical stability.
[0017] In the composite material prepared by the present invention, transition metal nitrogen / phosphide forms a heterogeneous structure, generates lattice mismatch and strong electron recombination, thereby improving the intrinsic activity of the composite material.
[0018] In the composite material prepared by the present invention, the electronic structure at the interface is regulated by combining transition metal nitrogen / phosphide, so that the composite material increases the OER performance while improving the excellent HER performance of the transition metal nitride.
[0019] The transition metal nitrogen / phosphide heterostructure micro-nano array composite material prepared by the present invention has dual-functional HER and OER electrocatalytic performance, and has the advantages of high activity, low voltage, high current density, stable performance, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 Figure 1 is a morphology characterization diagram of the NiCoP / NiMoN / NF-1200s composite material prepared in Example 1 of the present invention, wherein 1a is a SEM image, Figure 1 b is TEM image; Figure 2 The performance test diagram of the NiCoP / NiMoN / NF-1200s composite material prepared in Example 1 of the present invention as a catalyst in the electrochemical hydrogen evolution and oxygen evolution reactions. 2a is the HER polarization curve in 1 M KOH - 25°C electrolyte, 2b is the OER polarization curve in 1 M KOH - 25°C electrolyte, and the scanning rate is 1 mV / s. 2c is the stability test diagram of HER and OER in 1 M KOH - 25°C electrolyte; Figure 3 The performance test diagram of the NiCoP / NiMoN / NF-1200s composite material prepared in Example 1 of the present invention as a catalyst in the electrocatalytic water splitting reaction. 3a is the water splitting polarization curve in 30% KOH - 60°C electrolyte, with a scan rate of 1 mV / s, and 3b is the stability test diagram of water splitting in 30% KOH - 60°C KOH electrolyte; Figure 4 This is a high magnification SEM image of the NiCoP / NiMoN / NF-600s composite material prepared in Example 2 of the present invention; Figure 5 The performance test diagram of the NiCoP / NiMoN / NF-600s composite material prepared in Example 2 of the present invention as a catalyst in the electrochemical hydrogen evolution and oxygen evolution reactions. 5a is the HER polarization curve in 1 M KOH - 25°C electrolyte, 5b is the OER polarization curve in 1 M KOH - 25°C electrolyte, and the scan rate is 1 mV / s; Figure 6 This is the water splitting polarization curve of the NiCoP / NiMoN / NF-600s composite material prepared in Example 2 of the present invention as a catalyst in a 30% KOH - 60°C electrolyte, with a scan rate of 1 mV / s; Figure 7 This is a high magnification SEM image of the NiCoP / NiMoN / NF-1800s composite material prepared in Example 3 of the present invention; Figure 8 The performance test diagram of the NiCoP / NiMoN / NF-1800s composite material prepared in Example 3 of the present invention as a catalyst in the electrochemical hydrogen evolution and oxygen evolution reactions. 8a is the HER polarization curve in 1 M KOH - 25 ° C electrolyte, 8b is the OER polarization curve in 1 M KOH - 25 ° C electrolyte, and the scan rate is 1 mV / s; Fig. 9This is the water splitting polarization curve of the NiCoP / NiMoN / NF-1800s composite material prepared in Example 3 of the present invention as a catalyst in a 30% KOH - 60°C electrolyte, with a scan rate of 1 mV / s; Fig.10 This is a SEM image of the NiCoP / NF-1200s composite material prepared in Comparative Example 1 of the present invention; Fig.11 The performance test diagram of the NiCoP / NF-1200s composite material prepared in Comparative Example 1 of the present invention as a catalyst in electrochemical hydrogen evolution and oxygen evolution reactions. 11a is the HER polarization curve in 1 M KOH - 25°C electrolyte, 11b is the OER polarization curve in 1 M KOH - 25°C electrolyte, and the scanning rate is 1 mV / s; Fig.12 The SEM images of the NiMoN / NF composite material prepared in Comparative Example 2 of the present invention are shown in Figure 12a, where 12a is a low-magnification full-view image and 12b is a high-magnification morphology image. DETAILED DESCRIPTION
[0021] In order to gain a deeper understanding of the present invention, we will provide a comprehensive and detailed description of the present invention. However, the present invention has multiple implementations and is not limited to the specific examples listed herein. The presentation of these examples is intended to deepen the comprehensive understanding of the disclosure of the present invention.
[0022] A method for preparing a water splitting electrocatalyst
[0023] Step 1, hydrothermal reaction: 0.582-2.328 g of metal nitrate and 0.353-1.412 g of polyoxometalate were added to 30 mL of deionized water, ultrasonicated for 60 min, and then placed in a 12 cm 2 The metal foam is transferred to a hydrothermal reactor for heating reaction at a temperature of 150-170°C for a reaction time of 6-12 h. After the reaction is completed, the hydrothermal reactor is cooled, and the metal foam is taken out and placed in an oven for drying for 6 h. Step 2, nitridation treatment: set the temperature of the tube furnace to 500-700°C, the gas flow rate to Ar: 200±5 sccm, NH3: 100±5 sccm, and the total gas pressure to 2.2±0.1 Torr; place the metal foam obtained in step (1) in the center of the tube furnace, and heat treat at high temperature for 1-3 hours to obtain a transition metal nitride template supported by the metal foam; Step 3, electrochemical deposition: 0.175-1.223 g of metal nitrate and 0.636-4.452 g of NaH2PO2·H2O are added to 60 mL of deionized water, and after ultrasonic treatment for 30 min, the mixture is transferred to an electrolytic cell. The metal foam prepared in step (2) is used as the working electrode, the platinum sheet is used as the counter electrode, and Ag / AgCl is used as the reference electrode. A three-electrode system is used for constant voltage deposition. The deposition voltage is -0.8 to -1.2 V, and the reaction time is 180 to 1800 s. After the reaction is completed, the metal foam is taken out and placed in an oven for drying for 3 h, thereby obtaining a transition metal nitrogen / phosphide composite material supported by the metal foam.
[0024] Example 1 Preparation of water splitting electrocatalyst (1) Hydrothermal reaction: 1.164 g Ni(NO3)2·6H2O, 0.706 g (NH4)6Mo7O 24 ·4H2O was added to 30 mL of deionized water, ultrasonicated for 60 min, and then placed in a 12 cm 2 Pure nickel foam (NF) was transferred to a hydrothermal reactor for heating reaction at a temperature of 150 °C and a reaction time of 6 h. After the reaction was completed, the hydrothermal reactor was cooled, and the nickel foam was taken out and placed in an oven for drying for 6 h.
[0025] (2) Nitriding treatment: set the temperature of the tubular furnace to 500°C, the gas flow rates of Ar: 200 sccm, NH3: 100 sccm, and the total gas pressure to 2.2 Torr; place the nickel foam obtained in step (1) in the center of the tubular furnace, and heat treat at high temperature for 2 h to obtain a transition metal nitride template (NiMoN / NF) supported by nickel foam.
[0026] (3) Electrochemical deposition: 0.524 g Ni(NO3)2·6H2O, 0.524 g Co(NO3)2·6H2O, and 3.180 g NaH2PO2·H2O were added to 60 mL deionized water, and the mixture was ultrasonicated for 30 min before being transferred to an electrolytic cell. The nickel foam prepared in step (2) was used as the working electrode, the platinum sheet was used as the counter electrode, and Ag / AgCl was used as the reference electrode. The deposition was carried out using a three-electrode system with a constant potential of -1.0 V and a reaction time of 1200 s. After the reaction was completed, the nickel foam was taken out and dried in an oven for 3 h to obtain a nickel foam-supported transition metal nitrogen / phosphide composite material (NiCoP / NiMoN / NF-1200s).
[0027] like Figure 1 a and 1b are electron micrographs of the composite material, indicating that NiCoP / NiMoN / NF-1200s is uniformly loaded on nickel foam, presenting a hierarchical core-shell heterostructure micro-nano array.
[0028] like Figure 2 a and 2b are the HER and OER polarization curves of the composite material as a catalyst in 1 M KOH - 25 ° C electrolyte, respectively. It can be seen that the catalyst has a good performance at a current density of 1 A cm -2 The overpotentials of HER and OER are only 126 and 430 mV, respectively. Figure 2 c can be seen at 1 A cm -2 The stability of the composite materials HER and OER prepared by the invention can reach more than 150 h, proving that the bifunctional catalyst exhibits good hydrogen and oxygen evolution properties.
[0029] like Figure 3 As shown in a, the water splitting polarization curve of the composite material as a catalyst in 30% KOH - 60℃ electrolyte. It can be seen that the current density of the catalyst in 30% KOH - 60℃ electrolyte is 1 A cm -2 The required voltage is only 1.71 V. Figure 3 b It can be seen that at 1 A cm -2 The composite material prepared by the invention has a water splitting stability of more than 1500 h in 30% KOH-60℃ electrolyte, proving that the bifunctional catalyst exhibits good water splitting performance.
[0030] Example 2
[0031] The difference from Example 1 is that in step (3), the voltage deposition time is 600 s, and a transition metal nitrogen / phosphide composite material supported by nickel foam (NiCoP / NiMoN / NF-600s) is obtained.
[0032] like Figure 4 As shown, it is a scanning electron microscope (SEM) image of the composite material, indicating that NiCoP / NiMoN / NF-600s is uniformly loaded on the nickel foam, presenting a hierarchical core-shell heterogeneous structure micro-nano array.
[0033] like Figure 5 5a and 5b are the HER and OER polarization curves of the composite material as a catalyst in 1 M KOH - 25 ° C electrolyte, respectively. It can be seen that the catalyst has a good performance at a current density of 1 A cm -2 The overpotentials of HER and OER are only 147 and 480 mV, respectively, proving that the bifunctional catalyst exhibits good hydrogen and oxygen evolution performance.
[0034] like Figure 6As shown, the water splitting polarization curve of the composite material as a catalyst in 30% KOH - 60℃ electrolyte. It can be seen that the current density of the catalyst in 30% KOH - 60℃ electrolyte is 1 A cm -2 The required voltage was only 1.74 V, demonstrating that the bifunctional catalyst exhibited good water splitting performance.
[0035] Example 3
[0036] The difference from Example 1 is that in step (3), the voltage deposition time is 1800 s, and a transition metal nitrogen / phosphide composite material supported by nickel foam (NiCoP / NiMoN / NF-1800s) is obtained.
[0037] like Figure 7 As shown, it is a scanning electron microscope (SEM) image of the composite material, indicating that NiCoP / NiMoN / NF-1800s is uniformly loaded on the nickel foam, presenting a hierarchical core-shell heterogeneous structure micro-nano array.
[0038] like Figure 8 8a and 8b are the HER and OER polarization curves of the composite material as a catalyst in 1M KOH-25℃ electrolyte, respectively. It can be seen that the catalyst has a good performance at a current density of 1 A cm -2 The overpotentials of HER and OER are only 154 and 610 mV, respectively, proving that the bifunctional catalyst exhibits good hydrogen and oxygen evolution performance.
[0039] like Fig. 9 As shown, the water splitting polarization curve of the composite material as a catalyst in 30% KOH - 60℃ electrolyte. It can be seen that the current density of the catalyst in 30% KOH - 60℃ electrolyte is 1 A cm -2 The required voltage was only 1.75 V, demonstrating that the bifunctional catalyst exhibited good water splitting performance.
[0040] Example 4
[0041] The difference from Example 1 is that in step (1), 1.164 g Ni(NO3)2·6H2O and 0.706 g (NH4)6Mo7O 24 ·4H2O is replaced by 2.328 g Ni(NO3)2·6H2O, 1.412 g (NH4)6Mo7O 24 ·4H2O, and the nickel foam-supported transition metal nitrogen / phosphide composite material (NiCoP / NiMoN-1.5 / NF) was prepared.
[0042] The catalyst morphology and performance are the same as those in Example 1.
[0043] Example 5
[0044] The difference from Example 1 is that in step (1), the hydrothermal reaction conditions of 150°C-6h are replaced by 170°C-12h to obtain a nickel foam-supported transition metal nitrogen / phosphide composite material (NiCoP / NiMoN-170 / NF).
[0045] The catalyst has a current density of 1 A cm in 30% KOH-60℃ electrolyte. -2 The required voltage is only 1.78 V, proving that the bifunctional catalyst exhibits good water splitting performance.
[0046] Example 6
[0047] The difference from Example 1 is that in step (2), the temperature of the tube furnace is replaced by 700° C. instead of 500° C. to obtain a nickel foam-supported transition metal nitrogen / phosphide composite material (NiCoP / NiMoN-700 / NF).
[0048] The catalyst has a current density of 1 A cm in 30% KOH-60℃ electrolyte. -2 The required voltage is only 1.78 V, and the reaction can last for 1000 h, proving that the bifunctional catalyst exhibits good water splitting performance.
[0049] Example 7
[0050] The difference from Example 1 is that in step (3), the deposition voltage -1 V is replaced by -0.8 V to obtain a nickel foam-supported transition metal nitrogen / phosphide composite material (NiCoP / NiMoN / NF-(-0.8V)).
[0051] The catalyst morphology and performance are the same as those in Example 1.
[0052] Example 8
[0053] The difference from Example 1 is that in step (3), 0.524 g Co(NO3)2·6H2O is replaced by 0.582 g Fe(NO3)3·9H2O to prepare a nickel foam-supported transition metal nitrogen / phosphide composite material (NiFeP / NiMoN / NF).
[0054] The catalyst has a current density of 1 A cm in 30% KOH-60℃ electrolyte. -2 The required voltage is only 1.76 V, and the reaction can last for 1000 h, proving that the bifunctional catalyst exhibits good water splitting performance.
[0055] Example 9
[0056] The difference from Example 1 is that in step (1), the nickel foam is replaced by iron foam to obtain an iron foam-supported transition metal nitrogen / phosphide composite material (NiCoP / NiMoN / IF).
[0057] The catalyst has a current density of 1 A cm in 30% KOH-60℃ electrolyte. -2 The required voltage is only 1.72 V, and the reaction can be sustained for 1000 h, proving that the bifunctional catalyst exhibits good water splitting performance.
[0058] Comparative Example 1 The difference from Example 1 is that step 1 and step 2 are not involved, and electrochemical deposition is directly performed using pure nickel foam as the working electrode, so as to obtain a nickel foam-supported transition metal phosphide material (NiCoP / NF-1200s).
[0059] like Fig.10 As shown, it is a scanning electron microscope (SEM) image of the composite material, which shows that NiCoP / NF-1200s is accumulated on the nickel foam, proving that the transition metal phosphide cannot be uniformly dispersed on the pure nickel foam substrate without the transition metal nitride as a template.
[0060] like Fig.11 a and 11b are the HER and OER polarization curves of the composite material as a catalyst in 1M KOH-25℃ electrolyte, respectively. It can be seen that the catalyst has a good performance at a current density of 1 A cm -2 The overpotentials of HER and OER are only 338 and 720 mV, respectively, which proves that the hydrogen and oxygen evolution performances of transition metal phosphide materials loaded only on nickel foam without transition metal nitride as template are poor.
[0061] Comparative Example 2 The difference from Example 1 is that only the hydrothermal reaction of step (1) and the nitridation treatment of step (2) are performed, and the electrochemical deposition of step (3) is not involved.
[0062] like Fig.12 a and 12b are scanning electron microscope (SEM) images of the composite material, which prove that the firework-like rough surface of NiMoN nanorods can provide a large specific surface area, which is conducive to the subsequent growth of transition metal phosphides on its surface.
[0063] Example 10
[0064] Application of the metal foam-supported transition metal nitrogen / phosphide composite material as a catalyst in a water splitting reaction: Electrochemical tests were performed using a two-electrode or three-electrode system on an electrochemical workstation (CHI 660E). The composite material obtained in Example 1 was cut into 1 cm2 The working electrodes were inserted into 1 M KOH - 25℃ or 30% KOH - 60℃ electrolyte as anode and cathode, respectively.
[0065] Hydrogen evolution reaction (HER), oxygen evolution reaction (OER) test: In KOH electrolyte solutions with different concentrations, a three-electrode system was formed using a carbon rod as a counter electrode, a saturated calomel electrode as a reference electrode, and the water splitting electrocatalyst prepared by the invention as a working electrode to test the HER and OER performance. Linear sweep voltammetry (LSV) was tested at a scan rate of 1 mV / s, and all potentials were converted to standard hydrogen potential (RHE): E(RHE) =E(SCE) + (0.242+0.059pH).
[0066] Water splitting reaction test: In KOH electrolyte solutions with different concentrations, the water splitting electrocatalyst prepared by the invention was used as anode and cathode to form a two-electrode system to test the water splitting performance. Linear sweep voltammetry (LSV) was tested at a scan rate of 1 mV / s.
[0067] The contents not described in detail in the specification of the present invention belong to the prior art known to the professional and technical personnel in the field. Although the illustrative specific embodiments of the present invention are described above to facilitate the understanding of the present invention by the technical personnel in the field, it should be clear that the present invention is not limited to the scope of the specific embodiments. For the ordinary technical personnel in the field, as long as various changes are within the spirit and scope of the present invention defined and determined by the attached claims, these changes are obvious, and all inventions and creations using the concept of the present invention are protected.
Claims
1. A water splitting electrocatalyst, characterized in that: The catalyst is a transition metal nitrogen / phosphide composite material with metal foam as the substrate, which is in the shape of fireworks and is evenly loaded on the metal foam.
2. A water splitting electrocatalyst according to claim 1, characterized in that: In the transition metal nitrogen / phosphide composite material, the transition metal phosphide is a nanosheet, the transition metal nitride is a nanorod with a rough surface, the transition metal phosphide nanosheet grows vertically and uniformly on the surface of the transition metal nitride nanorod; the transition metal phosphide and the transition metal nitride are formed separately, and the two form a hierarchical core-shell heterostructure micro-nano array.
3. A water splitting electrocatalyst according to claim 1, characterized in that: The electrocatalyst is a transition metal nitrogen / phosphide composite material supported by metal foam synthesized by hydrothermal, nitridation and electrochemical deposition.
4. A method for preparing a water splitting electrocatalyst, characterized in that: The following steps are involved: Step 1, adding metal nitrate and polyoxometalate into deionized water and ultrasonicating them, then placing them into a metal foam substrate for hydrothermal reaction, cooling and drying them to obtain a precursor; Step 2, nitriding the precursor obtained in step 1 to obtain a transition metal nitride template supported by metal foam; Step 3, adding metal nitrate and sodium hypophosphite to deionized water, and transferring to an electrolytic cell after ultrasonication; using a transition metal nitride template supported by metal foam as a working electrode, a platinum sheet as a counter electrode, and Ag / AgCl as a reference electrode, a three-electrode system is used for constant voltage deposition, and after drying, a transition metal nitrogen / phosphide composite material supported by metal foam is obtained.
5. The method for preparing a water splitting electrocatalyst according to claim 4, characterized in that: In the preparation method, metal nitrate and polymetallic acid salt are used as metal sources, ammonia gas is used as nitrogen source, and sodium hypophosphite is used as phosphorus source.
6. The method for preparing a water splitting electrocatalyst according to claim 4, characterized in that: The metal nitrate is selected from ferric nitrate, cobalt nitrate or nickel nitrate; the polyoxometalate is selected from ammonium molybdate or ammonium tungstate; and the metal foam is selected from nickel foam, iron foam or copper foam.
7. The method for preparing a water splitting electrocatalyst according to claim 4, characterized in that: The mass ratio of metal nitrate to polyoxometalate in step 1 is 582-2328:353-1412; the reaction temperature of the hydrothermal reaction in step 1 is 150-170° C., and the reaction time is 6-12 h.
8. The method for preparing a water splitting electrocatalyst according to claim 4, characterized in that: In the step 2, the temperature of the nitriding treatment is 500-700° C., and the reaction time is 1-3 h. In the step 2, the environment of the nitriding treatment is argon as the protective gas, ammonia as the nitrogen source, and the argon / ammonia flow rate ratio is 2:
1.
9. The method for preparing a water splitting electrocatalyst according to claim 4, characterized in that: In the step 3, the mass ratio of metal nitrate to sodium hypophosphite is 175-1223:636-4452; the deposition voltage of the constant voltage deposition in the step 3 is -0.8-1.2 V, and the reaction time is 180-1800 s.
10. Use of the water splitting electrocatalyst prepared by the preparation method according to any one of claims 4 to 9 in the electrolysis of water for hydrogen evolution and oxygen evolution, characterized in that: The electrolysis environment of the water electrolysis reaction is 1 M KOH - 25°C or 30% KOH - 60°C.